Fostering Public Army Relation in Nepal - Duwadi, Eak Prasad (Unity Journal, 2021)
Nepal maintained army strength even during the reigns of Lichchavi kings. Later, its operations began to generate income. The way in which King Prithvi Narayan Shah and his successors diligently mastered the art of warfare and strategy resulted in the success of the Gorkhali army. After the Kot Prava, the Rana family emerged and radically changed policies. This research studies on Nepali Army’s glorious history, transformation, and mainly its public relation. The Postmodern Military Model (PMMM) is the theoretical perspective that has guided this study. For this, a qualitative method that deals with subjectivity is adopted. Secondary data such as journals, books and standard websites are used to analyze the data. Nepali Army is not a threat to the society that it protects as it has been trying to build its trust and credibility among the public. During its Imperial Era, the Great Britain awarded several Grukha soldiers in its military the ‘Victoria Cross’ for their unparalleled bravery and courage in various battles. Nepali Army gets exposure to serve in the outside world for decades. Relation between civil and army has not been bad in Nepal for many centuries despite of having some rubbings in the modern Nepal. However, politicians, notably the sitting PM or Defense Minister, routinely try to invoke the Nepal Army and draw it into the political jurisdiction. Nepali Army has been doing its duties honestly and unfailingly both inside and outside Nepal.